1987
DOI: 10.1016/0741-5214(87)90040-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of angiodynography to quantify blood flow in the canine aorta

Abstract: Previous attempts to quantify blood flow by means of ultrasound have been hampered by inaccurate diameter measurements and failure to account for the parabolic nature of the cross-sectional velocity profile. Angiodynography (ADG) provides a B-mode image of vessel walls, and the outer flow envelope is constantly monitored to provide phasic diameter measurements throughout the cardiac cycle. Frequency shifts are color-coded to provide a real-time visual display of varying velocity patterns across the vessel lume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A previous study has explored the utility of a CDUS system that allows volume flow to be recorded in a simple manner without additional calculations. 1 Keagy and associates indicated that this system may be an accurate method of quantitating in vivo volumetric blood flow in relatively large vessels at phys· iologic flow rates. In many clinical and research applications, however, conditions are encountered that may adversely affect flow quantitation.…”
mentioning
confidence: 99%
“…A previous study has explored the utility of a CDUS system that allows volume flow to be recorded in a simple manner without additional calculations. 1 Keagy and associates indicated that this system may be an accurate method of quantitating in vivo volumetric blood flow in relatively large vessels at phys· iologic flow rates. In many clinical and research applications, however, conditions are encountered that may adversely affect flow quantitation.…”
mentioning
confidence: 99%